Apis mellifera vs Melipona beecheii Cuban polifloral honeys: A comparison based on their physicochemical parameters, chemical composition and biological properties. (January 2018) - Alvarez-Suarez, José M.; Giampieri, Francesca; Brenciani, Andrea; Mazzoni, Luca; Gasparrini, Massimiliano; González-Paramás, Ana M.; Santos-Buelga, Celestino; Morroni, Gianluca; Simoni, Serena; Forbes-Hernández, Tamara Y.; Afrin, Sadia; Giovanetti, Eleonora; et al.
Abstract: Several polifloral honeys from the Apis mellifera and Melipona beecheii bee were analyzed to evaluate their pollen profile, physicochemical parameters, chemical composition and their antioxidant and antimicrobial activity. Flavonoids and other phenolic derivatives, 16 compounds in Apis mellifera honeys and 19 compounds in Melipona beecheii honeys, were identified using the HPLC-DAD-ESI-MS/MS analysis. The physicochemical parameters were within the ranges reported for these honeys, showing some of the distinctive characteristics of M. beecheii honeys compared to A. mellifera honeys, such as their high moisture and acidity. M. beecheii honey showed the highest values of total antioxidant capacity and total phenolic, flavonoid, carotenoids, ascorbic acid, free amino acid and protein contents compared to A. mellifera honey. M. beecheii honey also exhibited a higher antimicrobial activity. Our result shows that M. beecheii honeys is an important source of bioactive compounds with relevant biological properties compared to A. mellifera honey. Highlights: M. beecheii honeys possess highest polyphenol content than A. mellifera honeys. M. beecheii honeys have highest total antioxidant capacity than A. mellifera honeys. M. beecheii honeys exhibit higher antimicrobial activity than A. mellifera honeys.